UJI AKTIVITAS ANTIOKSIDAN EKSTRAK GANGGANG HIJAU (Ulva lactuca L.) DENGAN VARIASI KONSENTRASI PELARUT ETANOL 60%, 75%, DAN 96% MENGGUNAKAN METODE DPPH (1,1-difenil-2-pikrilhidrazil) - Desti Kameliani; Nina Salamah; Any Guntarti (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2020)
Free radicals give a negative effect. According to earlier research, Spyrogyra and Ulva lactuca L. have an anti-oxidant activity. This research aim to knowing the extract potential of green algae (Ulva lactuca) with variety concentration solvent as anti-oxidant by DPPH method, and finding the price of IC50 ethanol extract which compared with Galat acid. Extraction technic was maseration with ethanol solvent 60%,75%, and 96% which is implemented a qualitative test of extract active compound of U. lactuca Antioxidant activity of U. lactuca extract measured with spektrofotometri by using DPPH (1,1-difenil-2-pikrilhidrazil) method to get percentation of free radical resistor. The analytical result using SPSS, statistically got 95% credibility (p=0,05). This research showed that activity of antioxidant ethanol extract 96% of U. lactuca was higher than ethanol extract 60% and 75%. Activity of antioxidant ethanol extract 60%,75%, and 96% which confirmed by value of IC50 continously are 441,70 mg/ml ; 242,10 mg/ml dan 2,04 mg/ml. Whereas the value of IC50 galat acid standard is 3,92 x 10-3mg/ml. Based on tests of conducted antioxidant activity, the gallic acid has a strong antioxidant power, U. lactuca have a very weak antioxidant power